Holey Graphene–Enabled Solvent-Free Preparation of Ultrahigh Mass Loading Selenium Cathodes for High Areal Capacity Lithium–Selenium Batteries - Plaza-Rivera, Christian O.; Viggiano, Rocco P.; Dornbusch, Donald A.; Wu, James J.; Connell, John W.; Lin, Yi (Frontiers in Energy Research, 2021)
Solvents and binders are typical requirements in conventional lithium ion battery electrode fabrication to enable intimate material mixing, mechanical robustness, and reproducibility. However, for high energy density conversion chemistry cathodes such as sulfur (S) and selenium (Se), the time-consuming solvent-based methods are proven unreliable to achieve high mass loading cathodes with sufficient quality. Here, we report a facile solvent-free and binder-free method to prepare high mass loading composite Se cathodes that is enabled by the use of holey graphene (hG) as a lightweight conductive scaffold. Holey graphene is a derivative of graphene and can be dry-pressed into robust discs by itself. It can also serve as a matrix to host materials such as Se for composite disc preparation in a mix-and-press process free of solvent and binder. The method allows the preparation of ultrahigh Se content cathodes (up to 90 wt% Se) and ultrahigh Se mass loading (up to 15.6 mg cm−2 in this work). These cathodes exhibit excellent Se utilization, high areal capacity (up to 9 mAh cm−2), and good rate performance. The dry-press approach also allows for the preparation of a layered composite cathode architecture, where a thin hG layer is inserted between the composite and the current collector to improve the electrical contact. A solvent-free approach is also used to prepare hG-based hybrids with metal sulfides to be incorporated into a composite cathode to help entrap soluble polyselenide intermediates. The hybrid material is compatible with the solvent-free mix-and-press electrode fabrication approach and shows promise in improving the Se retention. While further improvements are still required, this work demonstrates the outstanding potential of using this facile, solvent-free approach enabled by hG for fabrication of high-performance, high mass loading conversion chemistry cathodes.